Spiritual Resistance and Cultural Exchange: The Fulni-ô of Aguas Bellas in an Intercultural Context (London Journal of Research In Humanities and Social Sciences, 2025)
The article intertwines different themes: indigenous cultural resistance, indigenous spirituality, and urban neo-shamanism. Its central nucleus is a reflection on a relational experience - over ten years old - between representatives of an Indigenous people from the Northeast of Brazil, the Fulni-, whose territory is located in the municipality of guas Belas, inland part of the State of Pernambuco, and non-indigenous members of three Rio de Janeiro associations, Casa de la Coruja Branca (House of the Owl) , Parati ONG (Para ti, For You), Casa da Aguia (House of the Eagle), whose aim is to defend indigenous cultures and, at the same time, maintain shamanic traditions. This 10-year-old experience is significant as it provides a long-term perspective on the dynamics of the relationship between these groups. One of the two authors is, at the same time, active in the ParatiGuest House.
Keywords: Kenya.; professional regulation; public management; regulatory quality; socio-economic transformation; whole-of-government approach; Migration.; Culture; Gun Island; Environmental Crisis; Sundarbans; Legends.